Pencak Silat dalam Tari Wireng di Surakarta - Mathias Supriyanto (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2010)
Royal traditional arts are generally influenced by the power of the king. An example is Bedhaya Anglirmendhung. This royal traditional dance has a heroic theme. It depicts the fight of Raden Mas Said (Mangkunegara I) against Pangeran Mangkubumi I. In addition to this dance, there are many others which have heroic themes such as Wireng dance. In this type of dance, some of the dance compositions include two types of 'pencak silat' movements: stylized movements and pure movements as found in Bogis dance